Detection of Positive Gross Primary Production Extremes in Terrestrial Ecosystems of China During 1982–2015 and Analysis of Climate Contribution. Issue 9 (13th September 2018) - Wang, Miaomiao; Wang, Shaoqiang; Wang, Junbang; Yan, Hao; Mickler, Robert A.; Shi, Hao; He, Honglin; Huang, Mei; Zhou, Lei
Abstract: Gross primary productivity (GPP) quantifies the photosynthetic uptake of carbon by terrestrial ecosystems. High‐temperature extremes and associated droughts significantly reduce terrestrial ecosystem carbon uptake, but there is uncertainty as to whether climatic extremes can be beneficial to ecosystem carbon uptake. In this study, we used three ecological models: the Boreal Ecosystem Productivity Simulator, the Terrestrial Ecosystem Carbon flux model, and the Global Production Efficiency Model coupled with the Carbon Exchange between Vegetation, Soil, and the Atmosphere model, to simulate China's terrestrial ecosystem GPP during the study period of 1982–2015. Positive GPP extremes were identified on yearly scales and analyzed for their temperature, precipitation, and solar radiation attributions. We found that the 3 years of positive GPP extremes occurred in 1990, 1998, and 2013, with the detrended GPP anomalies of 0.4 PgC/year, 0.2 PgC/year, and 0.3 PgC/year, respectively. Maximum GPP years were associated with an increased carbon uptake in response to increasing temperature and solar radiation under adequate precipitation for plant growth. China's subtropical‐tropical monsoonal region, a region dominated by managed forests and agricultural lands, contributed the largest in GPP extremes and accounted for 46%, 50%, and 46% of the total detrended GPP anomalies in 1990, 1998, and 2013, respectively. Positive GPP extremes were associated with increasing temperature and solar radiation, indicating favorable positive climate extremes would be beneficial to carbon uptake in China's terrestrial ecosystem. This study provides a method to assess positive GPP extremes in response to global climate change. Key Points: Three years of positive gross primary production extreme events occurred in 1990, 1998, and 2013 in China during 1982–2015 Favorable climate extremes contributed to the positive gross primary production extreme events The subtropical‐tropical monsoonal region of China contributed the largest in gross primary production extremes during 1982–2015